2007
DOI: 10.1051/vetres:2006056
|View full text |Cite
|
Sign up to set email alerts
|

Feline calicivirus

Abstract: -Feline calicivirus (FCV) is an important and highly prevalent pathogen of cats. It belongs to the family Caliciviridae which includes other significant pathogens of man and animals. As an RNA virus, high polymerase error rates convey upon FCV a high genome plasticity, and allow the virus to respond rapidly to environmental selection pressures. This makes the virus very adaptable and has important implications for clinical disease and its control. Being genetically diverse, FCV is associated with a range of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
232
0
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(272 citation statements)
references
References 106 publications
6
232
0
17
Order By: Relevance
“…FCV virions are non-enveloped, with icosahedral capsids with 27 to 40nm in diameter and a single-stranded and positive polarity RNA as genome; and it belongs to the Vesivirus genus of the Caliciviridae family (RADFORD et al, 2007). The genome has approximately 7.7 Kb and is organized in three open reading frames (ORFs).…”
Section: Feline Calicivirus (Fcv)mentioning
confidence: 99%
See 3 more Smart Citations
“…FCV virions are non-enveloped, with icosahedral capsids with 27 to 40nm in diameter and a single-stranded and positive polarity RNA as genome; and it belongs to the Vesivirus genus of the Caliciviridae family (RADFORD et al, 2007). The genome has approximately 7.7 Kb and is organized in three open reading frames (ORFs).…”
Section: Feline Calicivirus (Fcv)mentioning
confidence: 99%
“…The regions B, D and F are conserved, whereas C and E are variable. Region E is subdivided into hypervariable regions (HVR_E; RADFORD et al, 2007RADFORD et al, , 2009). The genes encoding immunodominant epitopes are present in E region, inducing neutralizing antibodies in the host.…”
Section: Feline Calicivirus (Fcv)mentioning
confidence: 99%
See 2 more Smart Citations
“…Disinfectants are biocide substances that destroy microorganisms or inhibit their activity on inanimate objects or surfaces (McDonnell and Russell 1999). Previous studies (Doultree et al 1999;Duizer et al 2004a;Radford et al 2007) concluded that ethanol and quaternary ammonium-based products were ineffective disinfectants of FCV and the inactivation of FCV required high concentrations of sodium hypochlorite. MNV is sensitive both to alcohols and to bleach and its resistance to basic and acidic pHs as well as it longterm resistance at room temperature is higher than that of FCV (Cannon et al 2006;Belliot et al 2008;Park and Sobsey 2011).…”
Section: Introductionmentioning
confidence: 99%